Intestinal microbiome and metabolome analyses reveal metabolic disorders in the early stage of renal transplantation. (22nd October 2021) - Ma, Chiyu; He, Jingquan; Lai, Liusheng; Chen, Yumei; Xue, Wen; Chen, Jieping; Dai, Weier; Tang, Donge; Yan, Qiang; Dai, Yong
Abstract : This study reveals the potential relationship between gut microbes and metabolic pathways in kidney transplant patients. The enriched Enterococcus in transplant patients may be related to the accumulation of nephrotoxic molecules. Abstract : Renal transplantation is the most effective treatment for end-stage renal disease, but the long-term prognosis of organs after transplantation is not ideal. In recent years, the importance of gut microbes and metabolites in the study of disease mechanisms has gradually received attention. However, the coordination between gut microbes and the metabolism of renal transplant patients needs further study. We integrated 16s sequencing and metabolomics data to describe the changes in the serum and fecal metabolites of renal transplant patients. Our data revealed that the gut microbial diversity decreased and the relative abundance of many bacteria, such as Enterococcus and Streptococcus, significantly changed after transplantation. In addition, a large number of amino acids and peptides in serum and feces significantly changed, suggesting an abnormal amino acid metabolism after transplantation. Spearman's correlation analysis revealed the changes in the co-metabolism pattern between gut microbes and the host metabolism after transplantation. Furthermore, Enterococcus was found to be correlated with renal functions and metabolites reflecting renal damage. This study provides potential gut microbes and metabolites impacting renal health, which helps in understanding the renal damage in patients with kidney transplantation.